Implementation of Discipline Penalties as Sanctions Applied in the Correctional Realm for Violations of the Rules of Order by Convicts - Tajuddin, Mulyadi Alrianto (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Disciplinary punishment is given to convicts who violate the prison rules, in this case convicts who are suspected of violating the order must be subjected to a preliminary examination by the head of security before being subject to disciplinary sanctions in accordance with Article 12 paragraph (1) of the Ministerial Regulation and Human Rights. Number 6 of 2013 concerning Rules of State Prisons and Detention Centers. Disclipnary punishment are given to the aim of this research to find out and understand the implementation of disclipnary punisments againts prisoners who violate the rules and the efforts faced by officers in prviding guidance in overcoming discliplinary violations at the Merauke Class IIB Penitentiary.This research was conducted using an empirical juridical method that looks at laws and regulations as a benchmark and looks at facts that occur in the field, especially in Merauke Class IIB Prison. From the results of the study, Discipline for prison-assisted citizens in Merauke Class IIB Prison has not been effective in accordance with the Regulation of the Minister of Law and Human Rights Number 6 of 2013. The obstacles faced by Class IIB Prison are adequate facilities and infrastructure, factors from prisoners and lack of prison officers and efforts made are oral socialization and making billboards to inform prisoners about obligations and prohibitions so that assisted citizens know the laws or regulations in Merauke Class IIB Prison.